2020
DOI: 10.3390/atoms8030052
|View full text |Cite|
|
Sign up to set email alerts
|

Investigation of a Collisional Radiative Model for Laser-Produced Plasmas

Abstract: Plasmas of a variety of types can be described by the collisional radiative (CR) model developed by Colombant and Tonan. From the CR model, the ion distribution of a plasma at a given electron temperature and density can be found. This information is useful for further simulations, and due to this, the employment of a suitable CR model is important. Specifically, ionization bottlenecks, where there are enhanced populations of certain charge states, can be seen in these ion distributions, which in some applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Laser-induced breakdown spectroscopy is one of the well-known diagnostic techniques in which optical emission spectra (OES) coming from the plasma are recorded and analyzed for their characterization [6][7][8][9]. Also, the OES measurements coupled with a suitable collisional radiative (CR) model provide an efficient and noninvasive diagnostic tool to extract detailed information about plasma parameters (n e , T e ), the population distribution of various excited levels of emitting species in the plasma, etc [10][11][12][13][14]. In order to develop a CR model, we need to know the various processes occurring along with their rate coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-induced breakdown spectroscopy is one of the well-known diagnostic techniques in which optical emission spectra (OES) coming from the plasma are recorded and analyzed for their characterization [6][7][8][9]. Also, the OES measurements coupled with a suitable collisional radiative (CR) model provide an efficient and noninvasive diagnostic tool to extract detailed information about plasma parameters (n e , T e ), the population distribution of various excited levels of emitting species in the plasma, etc [10][11][12][13][14]. In order to develop a CR model, we need to know the various processes occurring along with their rate coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 shows the weightings applied to the spectra Pt + -Pt 5+ ion stages, for different times after plasma formation, obtained from the CR model. A modified version [27] of the original CR model by Colombant and Tonon was implemented, in which it was shown that the accuracy of estimating the charge state at which ionization bottlenecks occur could be improved by eliminating the occupancy factor, using a different exponent value in the radiative recombination rate coefficient term, and by obtaining experimental values for ionization energies using the NIST database [1], where possible. Fractional ion composition of Pt plasmas with respect to electron temperature between 0 and 15 eV, at a constant electron density of 10 21 cm −3 , acquired using a collisional-radiative model by Colombant and Tonon [26].…”
Section: F Photoabsorption Of Platinum Ionsmentioning
confidence: 99%
“…The final paper [13] by Wong et al investigates the use of the Colombant and Tonon Collisional Radiative (CR) Model for the understanding of laser-produced plasmas. The CR model allows ion distributions for a given temperature and density to be calculated.…”
mentioning
confidence: 99%